(untitled) (Journal of Geography and Environmental Management, 2018)
The tourism industry of the 21st century has undergone radical changes due to latest information and communication technologies development. New technologies are an integral part of the recent trends in the tourist business – smart tourism, which is devoted to tourism information support both with informing consumers through Internet resources. Information support contributes to the formation of tourist flows and has an impact on the sustainable development of the regions. Reliable, accurate and up-to-date information is especially important for tourists who prefer individual travel planning. In the Russian Federation, the most complete and reliable information is provided by state tourist Internet services. They contain links to official sites of tourist sites. The traditional tourist object of Moscow is the Moscow State University. Accurate and up-to-date information about it for tourists, focused on in-depth study of places of visit, contains an online atlas of the “Territory of Moscow University”. The online atlas contains information about the historical and modern buildings of the university and also the territory belonging to the university. Different sections of the atlas are devoted to the geographical features, use and history of the Moscow State University campus. Particular role is played by aerial and space imagery which is a source of relevant spatial information. In a special section of the atlas in a popular form, the main information about aerial and space imagery of different types, the methods of their interpretation, examples of interpeted images of the university campus.